Prognostic impact of surgical margin in patients with hepatocellular carcinoma: A meta-analysis. Issue 37 (September 2017) - Zhong, Fu-Ping; Zhang, Yu-Jun; Liu, Ying; Zou, Shu-Bing
Abstract: Background: Surgical margin is an important prognostic factor in hepatectomy for patients with hepatocellular carcinoma (HCC). But the extent of surgical margins is still controversial. Our study was designed to systematically evaluate the prognosis of different width of resection margin. Methods: We conducted comprehensive searches of electronic databases including PubMed, MEDLINE, EMBASE, Cochrane, and the ISI Web of Science for relevant studies. A meta-analysis was performed by RevMan 5.3 software. Results: A total of 7 studies comprising 1932 patients were included. The patients with wider surgical margin were significantly higher than those with narrow surgical margin on 3-year overall survival (odds ratio [OR]: 1.58, 95% confidence interval (95% CI): 1.21–2.06, P  = .0008), 5-year overall survival (OR: 1.76, 95% CI: 1.20–2.59, P  = .004), 1-year disease-free survival (DFS)/recurrence-free survival (RFS) (OR: 1.43, 95% CI: 1.12–1.82, P  = .005), 3-year DFS/RFS (OR: 1.66, 95% CI: 1.35–2.03, P  < .00001), and 5-year DFS/RFS (OR: 1.69, 95% CI: 1.37–2.08, P  < .00001). There was no significant difference in the 1-year overall survival rate for the 2 groups (OR: 1.24, 95% CI: 0.89–1.72, P  = .20). Conclusion: In comparison with the narrow surgical margin group (<1 cm), the wide surgical margin (≥1 cm) can significantly improve the prognosis in patients with HCC.